MENINGKATKAN PRESTASI BELAJAR PERMUTASI DAN KOMBINASI MENGGUNAKAN MODEL PEMBELAJARAN JIGSAW - Rokhim, Abdul (Jurnal Analisis Pendidikan Sosial, 2024)
The purpose of this research is to improve the learning achievement of Permutations and Combinations using the Jigsaw learning model in class XII Electrical Engineering students of SMK Negeri 1 Bangil, Pasuruan Regency, 2017/2018 academic year. This research was conducted because of the low average value of learning achievement scores of class XII permutations and combinations of electricity at SMK Negeri 1 Bangil, Pasuruan district. This research is a classroom action research consisting of two cycles, in one cycle there are four stages, namely planning (planning), implementation / action (action), observation (observation), and reflection (reflection). The use of the Jigsaw learning model is intended to foster motivation and achievement in learning permutations and combinations in mathematics lessons for class XII SMK. After an evaluation was conducted through a written test, the data obtained, namely in the first cycle, the average grade value was 69.72 and from 36 students there were 22 students (61.1%) who had achieved a completeness score that was > 70. While in the second cycle the evaluation results obtained an average The average class is 79.58 and there are 34 students (94.4%) who have achieved a completeness score > 70. Thus, the use of the Jigsaw learning model can improve the learning achievement of permutations and combinations